Unbridled dreams - Whitson, Stephanie Grace (Bethany House Publishers, 2008)
Imogene Marshall has everything a girl could want--and she's miserable. To her, the perfect life is made of horses and cowboys and round-ups. When she's sent east to finishing school, Imogene disembarks on the way and ends up convincing Buffalo Bill himself to give her a chance in his Wild West Show. Imogene Marshall becomes "Liberty Belle," trick rider, and the object of attention from two cowboys who have very different ways of trying to win her heart. Determined to live her own dream, Liberty Belle travels across the country with one of them--but ends up in a place she couldn't have imagined even in her wildest dreams.